Sintesis dan Karakterisasi Senyawa BerstrukturAurivillius Empat dan Lima Lapis dan Penentuan Sifat Feroelektriknya - Edi Mikrianto; Ismunandar Ismunandar (Institut Teknologi Bandung, 2004)
Aurivillius oxides with composition of Na0,5Bi4,5Ti4O15 (NBT), K0,5Bi4,5Ti4O15 (KBT), Sr4Bi2Nb2Ti3O18 (SBNT), Ba4Bi2Nb2Ti3O18 (BBNT)and Bi5Ti5FeO18 (BTF) have been synthesised using the solid state reaction. The obtained oxides were polycrystalline. All the oxides were white, except that Bi5Ti5FeO18 was brick red in colour. Structure type determination was carried out using Phasanx software and PDF data base. It can be concluded that all oxides adopted orthorhombic crystal system and space group A21am with unit cell parameter a = 5.427(2) Ã , b = 5.459(3) Ã and c = 40.78(2) Ã for Na0,5Bi4,5Ti4O15; a = 5.430(1) Ã , b = 5.5258(6) Ã and c = 50.747(5) Ã for K0,5Bi4,5Ti4O15 ; a = 5.5439(9) Ã ; b = 5.5258(6) Ã and c = 50.747(5) Ã for Sr4Bi2Nb2Ti3O18 ; a = 5.540(2) Ã , b = 5.579(4) Ã and c = 50.962(8) Ã for Ba4Bi2Nb2Ti3O18 ; whilst for Bi5Ti5FeO18 a = 5.520(1) Ã , b = 5.569(3) Ã and c = 50.36(1) Ã . Ferroelectric properties measurement showed that polarization remanent Pr(+) and Pr(-) 0.049 Î¼Ccm-2 for Na0,5Bi4,5Ti4O15 ; 0.051 Î¼Ccm-2 for K0,5Bi4,5Ti4O15; 0.045 Î¼Ccm-2 for Sr4Bi2Nb2Ti3O18; 0.050 Î¼Ccm-2 for Ba4Bi2Nb2Ti3O18 and 0.050 Î¼Ccm-2 for Bi5Ti5FeO18.